Cyberlaw : A Study On The Computer Crime Act - Pathmanathan, Govindasamy (2002)

(untitled)
The world of information technology is growing tremendously. More and more computer users surf the cyberspace everyday. Advancement in communication technology enables the usage of Internet in various aspects of our daily live. Cyberspace is a space without boundary, law enforcement and virtual. Computers are used as a medium to surf this space with Internet technology. Various activities ranging from business, education, government ruling and others uses Internet. The wide usage of Internet imposes a new problem, computer crime. The law enforcement for computer crimes is categorized as Cyber Law. This is a very specific law to prevent unlawful activities involving the usage of computers. Cyber Law should be amended frequently along with the growth of Internet technology. This law has to be comprehensive. The definition used has to be precise to avoid any confusion. The definition analysis on computer crime act has to be conducted regularly. This is to ensure latest definition in the world of information technology is updated on a timely manner. Computer crimes can be prevented using prevention steps. These steps will help to curb these crimes.